Isolation and identification of soft coral-associated filamentous fungi from intertidal zones of Brgy. Uson, Caibiran, Biliran - Ocampo, Adrienne G. (2017)
Marine-derived fungi have been a focus of recent researches, particularly those associated with marine invertebrates such as soft corals, due to reports of enzymes and bioactive compounds that have promising biotechnological applications such as biodegradation, bioremediation, and bioaccumulation. With most studies on marine microorganisms being focused on bacteria, marine-derived fungi have been much underrepresented; hence, little is known about the fungal diversity associated with marine microorganisms, despite the important roles they play in marine ecosystems. This study is aimed to identify fungal diversity associated with soft coral from Biliran Island. Soft coral samples were collected and prepared according to described protocol from published literatures. These were plated in Potato Dextrose Agar (PDA), substituted with artificial seawater, and successive plate transfers were done to obtain pure cultures. The soft coral Sinularia sp. was identified through microscopic examination of its sclerites. Aspergillus and Penicillium were the only fungi isolated and identified through colony and microscopic morphological examination. Three Aspergillus species were observed based on the varying colony morphology: cottony white, powdery black and velvety dark green. The only Penicillium species observed had powdery olive-green colony. These were presumptive identification and could not be identified up to the species level since no physiological tests were done. Bothfungi have been previously cultivated from soft corals, including Sinularia, in studies that focused more on identification and production of secondary metabolites.